An Assessment of Patient Satisfaction and Decisional Regret in Patients Undergoing Staged Free-Flap Breast Reconstruction. Issue 5 (June 2021) - Shammas, Ronnie L.; Sergesketter, Amanda R.; Taskindoust, Mahsa; Glener, Adam D.; Cason, Roger W.; Hollins, Andrew; Atia, Andrew N.; Mundy, Lily R.; Hollenbeck, Scott T.
Abstract : Background: In the setting of radiation therapy or significant medical comorbidities, free-flap breast reconstruction may be intentionally delayed or staged with tissue expander placement ("delayed-immediate" approach). The effect of a staged approach on patient satisfaction and decisional regret remains unclear. Methods: All patients undergoing free-flap breast reconstruction (n = 334) between 2014 and 2019 were identified. Complication rates, patient satisfaction using the BREAST-Q, and decisional regret using the Decision Regret Scale were compared between patients undergoing immediate, delayed, and staged approaches. Results: Overall, 100 patients completed the BREAST-Q and Decision Regret Scale. BREAST-Q scores for psychosocial well-being ( P = 0.19), sexual well-being ( P = 0.26), satisfaction with breast ( P = 0.28), physical well-being (chest, P = 0.49), and physical well-being (abdomen, P = 0.42) did not significantly vary between patients undergoing delayed, staged, or immediate reconstruction. Overall, patients experienced low regret after reconstruction (mean score, 11.5 ± 17.1), and there was no significant difference in regret scores by reconstruction timing ( P = 0.09). Compared with normative BREAST-Q data, unlike immediate and delayed approaches, staged reconstruction was associated with lower sexual well-being ( P = 0.006). Furthermore, a significantly higher infection rate was seen among staged patients (immediate 0%, delayed 5%, staged 20%, P = 0.01). Conclusions: Staged free-flap breast reconstruction confers similar long-term satisfaction and decisional regret as immediate and delayed reconstruction but may be associated with worsened sexual well-being, when compared with normative data, and an increased risk of surgical site infection. When counseling patients regarding the timing of reconstruction, it is important to weigh these risks in the context of equivalent long-term satisfaction and decisional regret between immediate, delayed, and staged approaches. Abstract : Supplemental digital content is available in the text.